2012
DOI: 10.1080/1533256x.2012.647584
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Psychosocial Services Among Homeless Women Veterans

Abstract: Veterans comprise a disproportionate fraction of the nation's homeless population, with women veterans up to four times more likely to be homeless than non-veteran women. This paper provides a grounded description of barriers to psychosocial services among homeless women veterans. Three focus groups were held in Los Angeles, CA, with a total of 29 homeless women veterans. These women described three primary, proximal (current) barriers: lack of information about services, limited access to services, and lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…40 Another promising avenue for employment supports for women Veterans could be gender-specific adaptation and/or women Veteran-targeted implementation of Individualized Placement and Support (IPS), an evidence-based approach to returning individuals to competitive employment, mainly tested among individuals with serious mental illnesses (SMI), 41 including Veterans with SMI. For example, in keeping with a biopsychosocial approach to health and wellness, VA has extensive vocational rehabilitation and compensated work therapy programs that it administers as part of its comprehensive approach to the care of veterans with service-connected disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…40 Another promising avenue for employment supports for women Veterans could be gender-specific adaptation and/or women Veteran-targeted implementation of Individualized Placement and Support (IPS), an evidence-based approach to returning individuals to competitive employment, mainly tested among individuals with serious mental illnesses (SMI), 41 including Veterans with SMI. For example, in keeping with a biopsychosocial approach to health and wellness, VA has extensive vocational rehabilitation and compensated work therapy programs that it administers as part of its comprehensive approach to the care of veterans with service-connected disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while our results show high rates of engagement with mental health treatment, we do not have data on other psychosocial services, such as supportive housing or employment assistance that are essential for assisting homeless Veterans. A prior study of homeless women Veterans identified several barriers in access to psychosocial services,27 and future studies should assess utilization of services other than mental health care, and whether engagement may vary based on MST status and gender. Finally, though our data suggest that most Veterans who report MST are receiving mental health services addressing these experiences, we do not have information about the treatment approaches used by providers in delivering MST-related mental health care, nor the treatment outcomes of such approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we hypothesized that female gender would be associated with poor adherence. Indeed, female is a particularly vulnerable group, and initiation of treatment and monitoring are often difficult for them 47 48 49 . Female are in the minority of the homeless population and they often enter services at a much later stage than male, and when their problems have become more severe and enduring 50 .…”
Section: Discussionmentioning
confidence: 99%